2021
DOI: 10.1016/j.abrep.2021.100354
|View full text |Cite
|
Sign up to set email alerts
|

A discriminant analysis model of psychosocial predictors of problematic Internet use and cannabis use disorder in university students

Abstract: Highlights A discriminant analysis model of psychosocial factors was devised to differentiate between PIU and CUD. Compared to the control group, the PIU group had higher scores on motor, attentional and non-planning impulsiveness; tolerance of frustration, emotional pain, and ambiguity; negative and positive metacognitions, need to control thoughts, and cognitive confidence; and RNT. Compared to the control group, the CUD group had lower scores on family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 133 publications
1
6
0
Order By: Relevance
“…After review, no additional studies were found using the full DERS that met our criteria. Ten additional studies were found using different measures, but only eight met all other inclusion criteria: five studies using the ERQ [ 30 , 31 , 55 , 66 , 67 ] and three using shortened versions of the DERS [ 29 , 32 , 68 ]. We identified one study using the emotion regulation interview (ERI) [ 69 ] and another study using the emotion regulation skills questionnaire (ERSQ) [ 70 ]; these studies were not included in our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…After review, no additional studies were found using the full DERS that met our criteria. Ten additional studies were found using different measures, but only eight met all other inclusion criteria: five studies using the ERQ [ 30 , 31 , 55 , 66 , 67 ] and three using shortened versions of the DERS [ 29 , 32 , 68 ]. We identified one study using the emotion regulation interview (ERI) [ 69 ] and another study using the emotion regulation skills questionnaire (ERSQ) [ 70 ]; these studies were not included in our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, most participants were males, middle age, and single. Similarly, another study conducted to explore psychosocial predictors of addictive behaviors between Internet use and Cannabis use found that most participants were males aged over 20 [28]. Evidence denotes that excessive heavy Cannabis use among youth and middle-aged individuals is associated with several adverse health effects on physical and mental faculties [29].…”
Section: Discussionmentioning
confidence: 99%
“…The term “behavioral addictions”, which refers to the phenomena of non-chemical addictions ( Kardefelt-Winther et al, 2017 ), has three primary characteristics: Exposure to environmental stimuli for specific activities provoke psychophysiological reactions. ; engaging in the activity despite its negative effects; and the inability to cease the activity despite desiring to do so ( Akbari et al, 2021 ). Behavioral addictions share similarities with substance addictions in terms of symptoms and consequences, but in the former, there are no physical symptoms and substance use involved ( Alavi et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral addictions share similarities with substance addictions in terms of symptoms and consequences, but in the former, there are no physical symptoms and substance use involved ( Alavi et al, 2012 ). Various forms of behavioral addictions have been identified, including Gambling Disorder, problematic gaming, and problematic social media use ( Griffiths, 2005 , Akbari et al, 2021 ). Furthermore, it has been argued that compulsive shopping could be considered a form of behavioral addiction ( Griffiths, 2005 ).…”
Section: Introductionmentioning
confidence: 99%